Senior basketball players conformity - Vuckovic, I.; Gadzic, A. (Homosporticus, 2009)
Conformity as a form of players` behaviour toward coach and club management was the research topic of this study. This research had an aim to establish the differences in conformity degree between groups of basketball players, classified by three criterions: competitive level, player`s position and player`s age. Examinees sample was formed of 75 senior basketball players. Modified conformity scale was used as an instrument of research (The Conformity Scale, Mehrabian, & Stefl, 1995). Internal reliability of a modified scale was á=.74. Data was analized with help of non-parametrical Mann-Whitney test. Out of eight statements proposed, there were found significant differences in conformity degree between first leagued and second leagued players based on three statements. Among `outside` and `inside`, and younger and older players, there were no differences found based on any statement. Results indicate that examined Bosnian-Herzegovinian players are fond to conformity in great degree.